Clinical and epidemiological characteristics of children admitted with fever in emergency department with or without sepsis: Children with fever with or without sepsis - Costa de Santana, Mariana; Duarte Mello Amoedo, Caroline; Nascimento-Carvalho, Cristiana Maria (The Journal of Infection in Developing Countries, 2017)
Introduction: Sepsis is a major cause of childhood death worldwide. In developing countries, epidemiological data about sepsis is scarce. This study describes and compares the frequency of etiological agents and initial sites of infection in children with or without sepsis, identifying risk factors and assessing outcomes. Methodology: Clinical and demographic data from patients < 13 years of age with reported fever in a pediatric emergency department were collected and registered in forms. Patients were classified as with or without sepsis according to Goldstein et al.’s criteria [6]. Results: Of 254 patients, 120 (47%) did and 134 (53%) did not meet the sepsis definition. Overall, the median age (IQR) was 1.7 (0.8–3.9) years, and 153 (60%) were boys. Patients with sepsis were older (2.8 [1.1–5.3] versus 1.3 [0.6–2.9] years; p < 0.001) and had sickle-cell disease more frequently (7.6% versus 0.8%; p = 0.007). By multiple logistic regression, age and sickle-cell disease were independently associated with sepsis. The most frequent initial infections were pneumonia (43.7%), diarrhea (17.3%) and cellulitis/adenitis (13.0%). The frequency of these did not differ when patients with or without sepsis were compared. Etiology was established in 57 (22.4%) patients, 32 (26.7%), and 25 (18.7%) with or without sepsis, respectively. Four (3.3%) patients died in the sepsis subgroup, whereas none died in the other subgroup. Conclusions: Children who met the 2005 international consensus definition of sepsis showed differences in age and comorbidities (sickle-cell disease) upon admission and were more likely to die.